Efficacy and safety of a novel antiviral herbal preparation in ICU-admitted patients with COVID-19: A phase III double-blinded controlled trial - Hossein Faramarzi; Ahmad Hosseinpour; Amirhossein Sahebkar; Vahid Khaloo; Parisa Chamanpara; Mohammad Reza Heydari; Sajad Najafi; Fatemeh Fotoohi Khankahdany; Ahmad Movahedpour (Mashhad University of Medical Sciences, 2024)
Objective: Despite an increasing number of studies, there is as yet no definite treatment developed for the coronavirus disease 2019 (COVID-19). In this clinical trial, we examined the efficacy of a novel herbal antiviral preparation in critically ill COVID-19 patients.Materials and Methods: A total number of 120 ICU-admitted patients with a diagnosis of COVID-19 pneumonia were recruited to the trial. Participants were equally randomized to receive either the novel antiviral preparation sublingually, for up to two consecutive weeks or till discharge, or placebo. Clinical and laboratory parameters as well as survival rates were compared between the two groups.Results: The cumulative incidence of death throughout the study period was 8.33% in the intervention group and 60% in the placebo group (risk ratio: 0.14; 95% confidence interval [CI], 0.05 to 0.32; p<0.001). On day 7, several parameters including white blood cells (WBCs) count, C-reactive protein, and SpO2 were improved for the treatment group compared with the placebo group (p-values of 0.05, 0.01, and <0.001, respectively).Conclusion: This preparation might be suggested as a potentially promising COVID-19 treatment.